Implementation of Moral Aqidah Learning in Increasing Students' Social Intelligence at Madrasah Aliyah - Surani, Astaria; Uliyah, Taqwatul; Tamyis, Tamyis (CV. Tripe Konsultan, 2024)
Social intelligence is the ability to observe and understand the intentions, motivations and feelings of other people. Sensitive to other people's facial expressions, voices and body movements and able to respond effectively in communication. This research aims to examine the Implementation of Moral Aqidah Learning in Increasing Students' Social Intelligence in MA Hidayatul Mubtadiin Sidoharjo Jati Agung, South Lampung Regency in 2024. The type of approach used in this research is descriptive. Descriptive research is research that attempts to describe solutions to current problems based on data. The data collection techniques are: observation, interviews, and documentation. The data analysis techniques are: data reduction, data presentation (data presentation), and drawing conclusions/verification. Checking the validity of the data is: source triangulation, technical triangulation, and time triangulation. The research results show that by carrying out careful planning, effective implementation, and continuous evaluation, efforts are made to increase students' social intelligence. Learning moral beliefs at MA Hidayatul Mubtadiin in shaping students' character and personality, namely being able to create good relationships, be firm, and think before speaking or acting. To improve students' social intelligence, active involvement from various parties is needed, namely teacher support, madrasa regulations and support. from parents. Supporting factors are the presence of teaching staff, madrasa regulations, collaboration with parents and infrastructure. Meanwhile, the inhibiting factors are students who are less active and lack of time allocation.